Effect of Scrap Size on Extraction of Neodymium from Nd-Fe-B Magnet Scrap by Liquid Metal Extraction - Na, Hyun Woong; Kim, Yong Hwan; Taek Son, Hyeon; Ho Jung, In; Shin Choi, Han; Bum Kim, Tae (Current Nanoscience, 2014)
The effects of Nd-Fe-B magnet scrap size on extraction behavior were investigated by liquid metal extraction using molten Mg. The magnet scraps with Mg were placed into a stainless steel crucible and then heated to 1,073K for 10 to 50min. The amount of extracted Nd after liquid metal extraction process was increased with an increasing with holding time and scrap size, and the maximum contents of Nd in Mg were observed to be about 24.2 wt.% in the conditions of the 5mm sized scrap heated for 50min. It was revealed that Nd oxides existing in the magnet scraps prevent the dissolution of Nd into Mg.
Keywords: Extrusion rate